IMPROVEMENT OF THE LEGISLATIVE PROCESS IN THE AREA OF ECONOMY - Юлдашев, Сергій Олексійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to study the problems of lawmaking and to inform the leadership of the Verkhovna Rada, the country's leadership on the possibility, on the theoretical and methodological basis, to propose the solution of the main problems of lawmaking activity, management of the legislative process. It is proposed to develop and provide a model of effective management of the legislative process, to prepare a set of methodological materials regarding the implementation of legislative activity. Methods of research: general scientific which gave an opportunity to investigate the issues of improvement of law-making activity, normative-legal acts; the method of analysis and synthesis allowed in legal analysis to combine theoretical and practical shortcomings in the legislative activity of the Verkhovna Rada. Results: improvement of management of legislative activity in the sphere of management is proposed to be carried out on a powerful theoretical and methodological basis - systematic analysis; the identified shortcomings are the quality, inefficiency of the «original product», the ultimate activity of the VRU - its laws and regulations. Discussion: process problems - management of legislative activity (technology of preparation and adoption of legislative acts) in the sphere of management and management of the Verkhovna Rada should be considered comprehensively, systemically - as the only object of improvement - the object and the subject of management; problems in identifying the main shortcomings in the preparation and procedure of adopting these acts, in developing proposals for their elimination. It is emphasized that the complication of the management object - the economy of Ukraine, which is in a state of disrepair, necessitates raising the quality, efficiency of legislative activity, to a higher level, solving the existing problems of lawmaking. The level of requirements - on the one hand, and the complexity of problems that arise, on the other - make it necessary to apply (to solve the relevant problems) - a scientific methodology. B. a systematic analysis is proposed as the quality of such a methodology, which is characterized as a methodology for solving complex problems.